The relationship between isokinetic knee flexion andsquat jump performance - Gabriel Harčarik; Daniela Falat Leütterová (Journal of Kinesiology and Exercise Sciences)
BACKGROUND: Explosive power of the lower limbs is considered a powerful diagnostic method of the performance level of athletes. In the past, this issue has not yet been sufficiently explored. In the theoretical part, we tried using the available literature to approach the solved problem from the point of view of other authors. PURPOSE: The work aimed to verify and determine the existence of relationships between the isokinetic strength of the extensor joint and during the entire period in adolescent athletes of the Presov club. MATERIALS and METHODS: This study was carried out on adolescent athletes (n=21) who compete at the national level in the category of junior age. Average age 15.3 years, height 173 cm, weight 56 kg. Individual jumps SJ, CMJ, and CMJ FA were measured on Optojump. Isokinetic measurement of peak force and average force was performed in a bilateral version using a special adapter and IsoForce2 device at angular speeds of 50.s-1, 70.s-1, 90.s-1, 125.s-1, 155. s-1. We determined the relationships between individual variables using the Pearson correlation coefficient (r). RESULTS: Peak force values measured at an angular velocity of 155.s-1 on Izoforce2 correlated with SJ and CMJ jumps at the p < .05000 significance level. With average force values measured on isokinetic equipment, a significant relationship was demonstrated at an angular velocity of 155.s-1 in SJ, CMJ, and CMJ FA jumps at the level of significance p < .05000. The measured average values at an angular velocity of 125.s-1 were correlated at the level of significance p < .05000 only in SJ and CMJ FA jumps. CONCLUSIONS: The results of the work indicate that there is a relationship between vertical jumps and the values measured on isokinetic devices, which strengthens the claim about the importance of these muscle parts during the vertical jump as one of the limiting factors of performance in athletics. Due to the small number of people examined and the high variability of the results of similar studies, we recommend confirming the results that further measurements are also carried out at higher angular velocities of 180.s-1 to 230.s-1, in different periods of the athletes' training.